Utilization of information system towards resolving trust issue in zakat distribution - Shaari, Muhammad Shakirin; Che Mohd Arif, Ahmad Suki; Ta'a, Azman (2019)
Zakat is considered to be one of the five central pillar of Islam, the only one dealing directly with the social and economic aspect of the Islamic ummah. In order to achieve its intended objectives, it is critically important to ensure that the two major aspects of zakat management – collection and distribution is handled in the most effective way. Furthermore, the effectiveness of collection and distribution is very much dependent on the existence of the element of trust in the implementation of the two aspects. Increment in collection amount of zakat is very much dependent on the level of trust of zakat payer towards the zakat authority. Trust in turn, is very much a result of an effective zakat distribution mechanism. The central pivot of an effective zakat management thus revolves around the level of trust towards zakat implementation mechanism. This study proposes the usage of information technology to improve the implementation of zakat distribution which in turn increase the level of trust towards zakat management in Kedah. The increase level of trust will further trigger more collection from zakat payer. We have developed a model based on the current zakat management structure in Kedah. The model then will be used as the basis to create an information system specifically to simplify the process of asnaf identification and reporting in zakat distribution process.